‘Cold shock’ increases the frequency of homology directed repair gene editing in induced pluripotent stem cells - Q. Guo (Nature Portfolio, 2018)
Abstract Using CRISPR/Cas9 delivered as a RNA modality in conjunction with a lipid specifically formulated for large RNA molecules, we demonstrate that homology directed repair (HDR) rates between 20–40% can be achieved in induced pluripotent stem cells (iPSC). Furthermore, low HDR rates (between 1–20%) can be enhanced two- to ten-fold in both iPSCs and HEK293 cells by ‘cold shocking’ cells at 32 °C for 24–48 hours following transfection. This method can also increases the proportion of loci that have undergone complete sequence conversion across the donor sequence, or ‘perfect HDR’, as opposed to partial sequence conversion where nucleotides more distal to the CRISPR cut site are less efficiently incorporated (‘partial HDR’). We demonstrate that the structure of the single-stranded DNA oligo donor can influence the fidelity of HDR, with oligos symmetric with respect to the CRISPR cleavage site and complementary to the target strand being more efficient at directing ‘perfect HDR’ compared to asymmetric non-target strand complementary oligos. Our protocol represents an efficient method for making CRISPR-mediated, specific DNA sequence changes within the genome that will facilitate the rapid generation of genetic models of human disease in iPSCs as well as other genome engineered cell lines.